TARGET GAMES: SEBUAH PENGEMBANGAN KONSEP DIRI MELALUI PEMBELAJARAN PENDIDIKAN JASMANI - Aris Fajar Pambudi (Jurnal Pendidikan Jasmani Indonesia, 2010)
Abstract The study in this paper is an attempt to provide understanding and confidence on all sides that the development of positive self-concept that can be done through a program of physical education a meaningful learning. This paper will try to discuss about the role of games in order to target self-concept development through physical education learning. Target games are one game in TGfU classification that has different traits and characteristics with other forms of classification are themselves only with the ability that will determine the outcome. The hope is the development of positive self concept through target games in the physical education learning provided a useful provision for learners. Keywords: Target Games, Self-concept, Physical Education